Minimally invasive percutaneous plate osteosynthesis for the treatment of proximal humerus fractures in osteoporotic patients with Philos plate - Sahu, Ram ji Lal (Bangladesh Journal of Medical Science, 2013)
Introduction: To investigate the effect of minimally invasive percutaneous plate osteosynthesis for treatment of proximal humerus fractures in osteoporotic patients with philos plate. Methods: A prospective study was conducted at Department of Orthopedics, M.M.Medical College, Mullana Ambala, from July 2005 to November 2010. A Total of 108 cases of proximal humerus fractures were treated with minimally invasive percutaneous plate osteosynthesis with philos plate. According to Neer classification, 89 cases had two part fractures, 19 had tree part fractures. Results: All the 108 cases were followed up ranging from 12 to 18 months with an average of 14 months. Radio graphically, union was observed in 92 patients at the end of 10 weeks. In 10 patients, times to union were 16 weeks. Six patients underwent autogenous bone grafting because of nonunion after 16 weeks. The mean Constant-Murley score was 86 (range 74-92). The functional results of the shoulder, according to Muley scores, were classified as excellent in 85.15% cases, good in 9.25% cases and fair in 5.55 cases. Conclusion: Minimally invasive percutaneous plate osteosynthesis for treatment of proximal humerus fractures in osteoporotic patients with philos plate shows good results and less complication. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 140-145 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14941